Symptoms and signs of temporomandibular disorders among elderly Vietnamese. (December 2017) - Nguyen, Minh Son; Jagomägi, Triin; Nguyen, Toai; Saag, Mare; Voog-Oras, Ülle
Background: To assess the prevalence of the symptoms and signs of temporomandibular disorders (TMDs) and determine the prevalence of TMDs among elderly Vietnamese aged 65–74 years old. Methods: A cross-sectional study was conducted among 258 participants aged 65–74 years old (128 females and 130 males) using two strategies for TMD diagnosis: a clinical examination of the temporomandibular joint and its associated structures using the Diagnostic Criteria for Temporomandibular Disorders Axis I; and a set of 14 questions regarding TMD symptoms to obtain anamnestic data. Results: The prevalence of TMD symptoms was: headache 49.6%; temporomandibular joint noise 28.0%; orofacial pain 25.2%; jaw locking 3.1%; 62.5% of participants had at least one TMD symptom. Headaches were more prevalent in females than males ( p =0.009) and rural than urban residents ( p <0.001). The most frequent signs were temporomandibular joint crepitus (50.4%), clicking (48.1%) and mouth-opening deviation (37.6%). Temporomandibular joint crepitus and mouth-opening deviation were more frequent among rural than urban ( p =0.024 and p <0.001, respectively). TMD was found in 56.6% of the total sample. Of the TMD sufferers, 37.6% were diagnosed with disc displacement, 34.9% with degenerative joint disease, 3.5% with myalgia and 1.2% with arthralgia. Conclusions: More than half of elderly Vietnamese have at least one TMD symptom. TMD sounds were the most common clinical sign of TMD. There were no differences between the genders or place of residence and TMD diagnosis. Disc displacement and degenerative joint disease were most prevalent among elderly Vietnamese.